2021
DOI: 10.3390/vaccines9010033
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Antigen Display on PapMV Nanoparticles Influences Its Immunogenicity

Abstract: Background: The papaya mosaic virus (PapMV) vaccine platform is a rod-shaped nanoparticle made of the recombinant PapMV coat protein (CP) self-assembled around a noncoding single-stranded RNA (ssRNA) template. The PapMV nanoparticle induces innate immunity through stimulation of the Toll-like receptors (TLR) 7 and 8. The display of the vaccine antigen at the surface of the nanoparticle, associated with the co-stimulation signal via TLR7/8, ensures a strong stimulation of the immune response, which is ideal for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…Since the production platform we describe here does not require the resulting VLPs to be infectious, it may be possible to modify the particles more extensively than previously possible by modifying either the coat protein subunits, incorporating designer RNAs, or both. For example, PapMV, expressed in Escherichia coli and assembled on ssRNA in vitro, has been studied recently for its potential use as vaccine epitope carrier and adjuvant [ 32 , 33 , 34 ]. The use of plants as a production system may have benefits over bacterial expression, especially in the case of the display of peptides which may benefit from expression in a eukaryotic host.…”
Section: Discussionmentioning
confidence: 99%
“…Since the production platform we describe here does not require the resulting VLPs to be infectious, it may be possible to modify the particles more extensively than previously possible by modifying either the coat protein subunits, incorporating designer RNAs, or both. For example, PapMV, expressed in Escherichia coli and assembled on ssRNA in vitro, has been studied recently for its potential use as vaccine epitope carrier and adjuvant [ 32 , 33 , 34 ]. The use of plants as a production system may have benefits over bacterial expression, especially in the case of the display of peptides which may benefit from expression in a eukaryotic host.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the coupling density of M2e peptide onto the PapMV-N nanoparticles (made of PapMV CP with N-terminal acceptor site) could reach up to 83% by increasing the incubation time and the concentration of M2e peptide ( 22 ). However, in our system, the efficiency of SrtA-mediated ligation was only around 20% to 40% ( Figures 3C, F and 4D ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the previous designs, our current system exhibits several unique features. Firstly, the BaMV CVP scaffolds are produced in plants, as opposed to those produced in bacteria or animal cells ( 16 18 , 21 , 22 , 56 , 57 ). The plant production system reduced the risk of contamination from prokaryotic or animal sources, and allows for easy scale-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations